The Double Dividend Hypothesis of Environmental Taxes: A Survey - Ronnie Schöb (Center for Economic Studies and ifo Institute (CESifo), 2003)
This survey reviews the recent literature on the double-dividend hypothesis of environmental taxes and discusses some recent extensions of the standard model such as the distributional consequences and the importance of the non-separability assumption between consumption goods and environmental quality for the optimal design of environmental policies. Furthermore, the paper analyses alternative concepts of a double dividend by looking at the employment dividend in countries that suffer from involuntary unemployment, and rent-extracting dividends that resource-consuming countries can reap at the cost of resource-owning countries.
Keywords: 330